2019
DOI: 10.1038/s41467-018-08275-7
|View full text |Cite
|
Sign up to set email alerts
|

Resilience of the Eastern African electricity sector to climate driven changes in hydropower generation

Abstract: Notwithstanding current heavy dependence on gas-fired electricity generation in the Eastern African Power Pool (EAPP), hydropower is expected to play an essential role in improving electricity access in the region. Expansion planning of electricity infrastructure is critical to support investment and maintaining balanced consumer electricity prices. Variations in water availability due to a changing climate could leave hydro infrastructure stranded or result in underutilization of available resources. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 96 publications
(50 citation statements)
references
References 26 publications
0
47
0
Order By: Relevance
“…Lastly, we ranked the combinations based on their climate moisture index (CMI) [54]. The climate moisture index (CMI) is a measure of aridity that combines the effect of rainfall and temperature projections [55]. Since analyzing all the combinations was outside the scope of this study, we selected two climate change projections-wet and dry-as well as a business as usual (baseline) projection.…”
Section: Climatic Representationmentioning
confidence: 99%
See 1 more Smart Citation
“…Lastly, we ranked the combinations based on their climate moisture index (CMI) [54]. The climate moisture index (CMI) is a measure of aridity that combines the effect of rainfall and temperature projections [55]. Since analyzing all the combinations was outside the scope of this study, we selected two climate change projections-wet and dry-as well as a business as usual (baseline) projection.…”
Section: Climatic Representationmentioning
confidence: 99%
“…The index values varied between −1 and +1, with lower values representing more arid conditions. A CMI value greater than zero indicated that precipitation rates were greater than potential evapotranspiration rates [55,56]. It had to be taken into consideration that the chosen scenarios were cumulatively wet or dry but needed not be in all the years when compared to the baseline.…”
Section: Climatic Representationmentioning
confidence: 99%
“…This represents a great barrier to performing effective integrated assessment studies, developing modelling frameworks, and recommending policies for resilience building. While a multitude of studies have been carried out at the basin or global scale in terms of assessing the projected long-term impacts of climate change on hydropower generation potential [13][14][15][16][17][18] and on the discharge of rivers [19], only few have assessed the impact of hydro-climatic extreme events on power supply reliability [20][21][22] and the related impacts on electricity consumption. Moreover, researchers (see [23]) have recently highlighted the necessity of reconciling top-down and bottom-up approaches to climate and energy-related assessment, indicating that novel methodologiesincluding the use of earth observation data [24,25]are required.…”
Section: Introductionmentioning
confidence: 99%
“…As the energy crisis and environmental pollution problems intensify in the world, energy storage devices are receiving more and more attention as sustainable green energy storage devices. Renewable energy sources such as wind, solar, and hydropower are important ways to meet global electric power demand in a clean and green way . As a key equipment for building a global energy internet, energy storage is now receiving more and more attention from countries and regions.…”
Section: Introductionmentioning
confidence: 99%
“…Renewable energy sources such as wind, solar, and hydropower are important ways to meet global electric power demand in a clean and green way. [1][2][3] As a key equipment for building a global energy internet, energy storage is now receiving more and more attention from countries and regions. As one of the two main types of energy storage devices, supercapacitors (SCs) have many advantages over other storage devices, such as high power density and fast charge/discharge rate capacity.…”
Section: Introductionmentioning
confidence: 99%